The Effect of School Leadership and Management on the Performance of Teachers of the First High School in Air Kumbang Sub-District, Banyuasin District - Halim; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The purpose of this study was to determine and analyze the influence of leadership and management of school principals together on the performance of junior high school teachers in Air Kumbang District. The research method used in this research is descriptive quantitative research method. The instrument used in the study was a questionnaire. Testing requirements analysis hypothesis testing. There are 3 conditions that must be met before conducting regression analysis, namely 1) normality test; 2) homogeneity test; and 3) linearity test. Based on the results of the above research, it can be concluded that there is a significant influence between the leadership of the principal on the performance of teachers in SMP in Air Kumbang District, which means that the better the leadership of the principal, the better the performance of SMP teachers in Air Kumbang District . Thus it can be concluded that the second hypothesis is accepted. From the results of this study the authors suggest to other researchers, to examine the performance of teachers in Air Kumbang District, to include other variables such as motivation, compensation, level of education that can affect teacher performance.